Frequency of Measles-Infected Pneumonia in Chilren and Infants - Muhammad Muaz Ayub, Muhammad Mutaal Tahir, Muhammad Hasan Saeed, Muhammad Moiz Tahir, Noor Tahir, Muhammad Ali Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Measles-related pneumonia in children and newborns is the primary goal of this research. Study Design: Cross-sectional Place and Duration: Conducted at BHU 399 GB Tandlianwala in duration of July 2021-Jan 2022. Methods: This research covered a total of 125 patients, including children and newborns of both sexes. Children under the age of seven were present. After receiving official permission from the authorities, the demographics, height, and weight of the patients were recorded. Those who had been diagnosed with measles were brought in. All patients’ symptoms and frequency of pneumonia were evaluated. SPSS 24.0 version was used to analyze all of the data. Results: Majority were 70 (56%) children and there were 55 (44%) infants. Among 125 patients, 75 (60%) were males and 50 (40%) were females. Majority had birth weight <3kg. Severity of measles was found among 55 (44%) patients. Frequency of vaccination was found among 29 (23.2%) cases. Pneumonia was found in 77 (61.6%) cases. Conclusion: In this research, we found a considerably high frequency of measles-infected pneumonia. Patients with low socioeconomic position had a lower vaccination status, which contributed to the problem. It can be prevented by educating parents about the need of vaccinations.